MENTAL WORKLOAD ANALYSIS OF NAVAL CADET ACADEMY USING SUBJECTIVE WORKLOAD ASSESSMENT TECHNIQUE (SWAT) METHODS - Elisabeth Tanti Pudiastuti (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
There are plentiful activities conducted by the Cadets in order to hold educational process at the NavalAcademy. These activities are particularly vulnerable to physical and psychological friction, especiallyin routine and nurturing activities, where activities in this phase are thought to cause the Cadets toexperience excessive mental workloads which may result in the Cadets being unable to continue theireducation. Therefore, this research would identify one of the factors that were suspected to be thecause of the problem which was psychological factor or mental workload on the Academy of Navalusing Subjective Workload Asessesment Technique (SWAT) method. SWAT method was chosenbecause it was easier to apply and had some advantages in terms of results validity and accuracy, sothat the performance of Cadets expected by Institution were: Tanggap, Tanggon and Trengginas. Theresults of this study indicated that there was a high mental workload for some sub activities at somelevel. The highest mental workload in level I is 69,0 (RPS activity), in level II is 83,4 (senior juniordevelopment), in level III is 77,6 (senior junior development). Besides this research also showed thatthe mental workload between the four levels of Level I, II, III and IV had a significant difference inmental workload in carrying out every activity at the Academy.Keywords: Subjective Workload Assessment Technique (SWAT), Mental Workload, Cadets.